Effect of blended learning, motivation, study hour on student learning achievement - Jaka Sunardi; Soh Kim Geok; Komarudin Komarudin; Hari Yuliarto; Ranintya Meikahani (Jurnal Keolahragaan, 2021)
This research aims at determining the effect of blended learning, motivation, lesson hour on student achievement.The research method used is a survey method, with data collection techniques using a questionnaire. The population in this study were students of the Health and Recreation Physical Education Study Program, with a total of 221 UNY students and 188 UPM students. The data analysis technique used regression test. The results showed that (1) There was a significant influence between blended learning on the motivation of UNY and UPM students, (2) There was a significant influence between blended learning on the learning hours of UNY and UPM students, (3) There was a significant influence between blended learning on study hours of YSU and UPM students, (3) There is a significant influence between blended learning on the learning motivation of UNY and UPM students. There is a significant influence between blended learning on learning hours for both YSU and UPM students, (4) There is an influence between blended learning on student learning achievement even though it is weak, this shows that learning achievement is influenced by other variables not studied. Whereas for UPM there is a significant effect, but for the learning achievement variable it is influenced by other variables that are not researched, (5) There is a combined effect of blended learning, motivation, and study hours on UNY and UPM students, but the learning achievement variable is influenced by other factors or variables not studied.